2001
DOI: 10.1007/s002220000106
|View full text |Cite
|
Sign up to set email alerts
|

Compact Stein surfaces with boundary as branched covers of B 4

Abstract: We prove that Stein surfaces with boundary coincide up to orientation preserving diffeomorphisms with simple branched coverings of B 4 whose branch set is a positive braided surface. As a consequence, we have that a smooth oriented 3-manifold is Stein fillable iff it has a positive open-book decomposition.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(120 citation statements)
references
References 29 publications
0
119
0
Order By: Relevance
“…. ∪ h m , where X 0 consists of 0-and 1-handles and each h i , 1 ≤ i ≤ m, is a 2-handle attached to [25], also see Akbulut-Ozbagci [1]). An oriented compact 4-manifold with boundary is a Stein surface, up to orientation preserving diffeomorphisms, if and only if it admits an allowable Lefschetz fibration over the 2-disk, a.k.a "PALF".…”
Section: Stein Manifoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…. ∪ h m , where X 0 consists of 0-and 1-handles and each h i , 1 ≤ i ≤ m, is a 2-handle attached to [25], also see Akbulut-Ozbagci [1]). An oriented compact 4-manifold with boundary is a Stein surface, up to orientation preserving diffeomorphisms, if and only if it admits an allowable Lefschetz fibration over the 2-disk, a.k.a "PALF".…”
Section: Stein Manifoldsmentioning
confidence: 99%
“…Following the works of Eliashberg and Gompf on handle decompositions of compact Stein manifolds, Loi and Piergallini, proved that any Stein domain admits a Lefschetz fibration structure [25] (and an alternative proof was later given by Akbulut and Ozbagci [1]). Moreover, the Stein structure on an allowable Lefschetz fibration can be chosen so that the contact structure it induces on the boundary agrees with the one that the Thurston-Winkelnkemper construction would hand when applied to the natural open book induced by the Lefschetz fibration on the boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Building on Eliashberg's topological characterization of Stein fillings and the work of Rudolph on braided surfaces, they showed that every Stein filling come from an allowable Lefschetz fibration on X [26] (also see [1], and [8] for a further generalization to Lefschetz fibrations over arbitrary compact surfaces with non-empty boundaries), which arise as a branched covering of the Stein 4-ball along a braided surface S. On the other hand, the works of Rudolph [32] and Boileau and Orevkov [10] established that quasipositive links are precisely those which are oriented boundaries of smooth pieces of complex analytic curves in the unit 4-ball, realized as braided surfaces.…”
Section: Stein Fillings Allowable Lefschetz Fibrations and Braided Smentioning
confidence: 99%
“…By the pioneering works of Rudolph [32] and Boileau and Orevkov [10], these links are characterized as oriented boundaries of smooth pieces of complex analytic curves in the unit 4-ball -which can be realized as braided surfaces. An intimate connection between fillings of contact 3-manifolds and quasipositive braids is provided by Loi and Piergallini [26], who showed that every Stein filling of a contact 3-manifold is a branched cover of the Stein 4-ball along a braided surface.…”
Section: Introductionmentioning
confidence: 99%
“…If the monodromy (t α1 , t α2 , · · · , t αm ) transforms another m-tuple (t α ′ 1 , t α ′ 2 , · · · , t α ′ m ) by Hurwitz moves and total conjugations, we write Loi and Piergallini [17], and Akbulut and Ozbagci [1] showed that every open book decomposition with monodromy which has a positive factorization supports a Stein fillable contact structure, and every Stein fillable contact structure is supported by an open book decomposition with monodromy which has a positive factorization. It can be easily check that, for any PALF f : X → D 2 with fiber Σ, we obtain the open book decomposition with page Σ and monodromy the total monodromy of f .…”
Section: Preliminariesmentioning
confidence: 99%